2017
DOI: 10.1177/0271678x17725431
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypertensive response in patients with intracerebral hemorrhage pathophysiology and treatment

Abstract: Acute hypertensive response is a common systemic response to occurrence of intracerebral hemorrhage which has gained unique prominence due to high prevalence and association with hematoma expansion and increased mortality. Presumably, the higher systemic blood pressure predisposes to continued intraparenchymal hemorrhage by transmission of higher pressure to the damaged small arteries and may interact with hemostatic and inflammatory pathways. Therefore, intensive reduction of systolic blood pressure has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 100 publications
1
22
0
Order By: Relevance
“…Hypertension is the most frequent comorbidity associated with CNS injuries (Abraham et al ., 2016; Qureshi and Qureshi, 2017). Hypertension is evident in up to 70% of stroke patients (Staessen et al ., 2003).…”
Section: Pparγ Protects Against Comorbiditiesmentioning
confidence: 99%
“…Hypertension is the most frequent comorbidity associated with CNS injuries (Abraham et al ., 2016; Qureshi and Qureshi, 2017). Hypertension is evident in up to 70% of stroke patients (Staessen et al ., 2003).…”
Section: Pparγ Protects Against Comorbiditiesmentioning
confidence: 99%
“…Spontaneous intracerebral hemorrhage (SICH) remains a devastating disease without effective therapies, with only approximately 20% of patients achieving functional independence at 6 months ( van Asch et al, 2010 ). Recent studies have shown that the prognosis of SICH varies with the location of the haematoma, and clinical trials on this disease have begun to develop novel SICH treatments to target various populations to maximize treatment benefits ( Anderson et al, 2010 ; Fu et al, 2014 ; Sreekrishnan et al, 2016 ; Qureshi and Qureshi, 2018 ). To better make clinical decisions for these candidate therapies, it is essential to derive effective and reliable prognostic tools for the prognostic risk assessment of SICH.…”
Section: Introductionmentioning
confidence: 99%
“…Differences may be explained by the variation in intensity of SBP reduction between trials. A treatment threshold of SBP ≥180 mm with the target goal of reduction to 130–150 mmHg within 6 h of symptom onset may be best choice [ 152 ].…”
Section: Discussionmentioning
confidence: 99%